THE MANAGEMENT OF TEACHERS’ PERFORMANCE AT HIGH PERFORMING ISLAMIC SCHOOLS IN MALANG REGENCY - Muhadjir, M (Faculty of Education Universitas Negeri Malang, 2017)
The aim of the study was to find and give in-depth description of teachers’ performance in State Islamic Junior High School 3 Gondanglegi, State Islamic Junior High School Turen, and State Islamic Junior High School Lawang. The data was collected by using participant observation, in-depth interview, and documentation. The findings of the study were: (1) the teachers’ performance programs were planned by involving the stakeholders and were based on the vision, the mission, and the goals of the Islamic schools which were in line with the specialties and the characteristics of the Islamic schools, (2) teachers’ performance programs which were suitable with the lesson plan were carried out by the teachers. The implemented teaching and learning strategies varied based on the materials and the characteristics of the learners, (3) the evaluation model of the teachers’ performance was done by the principals by evaluating the sets of learning in the beginning of the academic year, supervising the ongoing teaching and learning in the classroom, evaluating the teachers’ performance through the teachers’ diary, giving questionnaire to and interviewing the students, and thoroughly evaluating by using DP3 form at the end of the academic year, (4) the good management of the teachers’ performance led to the improvement of the teachers’ professionalism and the improvement of the teachers’ professionalism led to the improvement of the students’ academic and non-academic achievement. Keywords: management, teachers' performance, high-performing Islamic schools